Marker-assisted pyramiding of leaf rust resistance genes Lr24 and Lr28 in wheat (Triticum aestivum) - CHHUNEJA, PARVEEN; VIKAL, YOGESH; KAUR, SATINDER; SINGH, RIPPY; JUNEJA, SHRUTI; BAINS, N S; BERRY, ONIKA; SHARMA, ACHLA; GUPTA, S K; CHARPE, A; PRABHU, K V; DHALIWAL, H S (The Indian Journal of Agricultural Sciences, 2011)
A study was undertaken to pyramid two effective leaf rust resistance genes Lr24 and Lr28 in ‘PBW 343’ wheat (Triticum aestivum L. emend. Fiori & Paol.) background, a ruling variety of North Western Plains Zone using marker assisted selection. ‘PBW343’ near isogenic lines with Lr24 and Lr28 developed through backcross breeding, were intercrossed and the marker assisted selection was conducted in the F1 to F4 segregating generations using SCAR markers S73719 and S421570 linked to Lr24 and Lr28 respectively. Homozygous pyramid lines were developed and evaluated in yield trials to assess the effect of these genes on yield parameters. Some of the pyramid lines were observed to have better yield potential than the recipient parent ‘PBW 343’ and no yield penalty was apparent in these lines. Selected lines are being used for combining stripe rust and stem rust resistance genes with leaf rust resistance through marker assisted selection.